TECHNOLOGY-ENHANCED LEARNING IN PRIMARY EDUCATION: EFFECTS OF INTERACTIVE DIGITAL PLATFORMS ON STUDENT ENGAGEMENT AND ACHIEVEMENT - Gonzales, Samantha; Flores, Josefa; Villanueva, Andres; Yani, Ahmad (International Journal of Educatio Elementaria and Psychologia, 2026)
Technology-enhanced learning has become increasingly prominent in primary education as schools integrate interactive digital platforms to support teaching and learning. These platforms are widely assumed to enhance student engagement and academic achievement, yet empirical evidence at the primary level remains uneven and context dependent. This study aims to examine the effects of interactive digital platforms on student engagement and academic achievement in primary education, with particular attention to the relationship between engagement dimensions and learning outcomes. The study employed a quantitative quasi-experimental design involving experimental and control groups of primary school students. Data were collected using engagement questionnaires, curriculum-aligned achievement tests, classroom observations, and academic records. Inferential statistical analyses were conducted to compare group differences and examine relationships between engagement and achievement. The findings reveal that students exposed to interactive digital platforms demonstrated significantly higher levels of behavioral, emotional, and cognitive engagement than those receiving conventional instruction. Academic achievement scores were also significantly higher in the experimental group. Correlation analysis indicates a strong positive relationship between student engagement and achievement outcomes. The study concludes that interactive digital platforms positively influence engagement-driven learning in primary education when integrated within structured pedagogical practices. Technology-enhanced learning is most effective when engagement functions as a central mechanism linking digital interaction to academic success.